Morphological Study of the Relationships between Weedy Rice Accessions (Oryza sativa Complex) and Commercial Rice Varieties in Pulau Pinang Rice Granary Area - Zainudin PMD Hussain; Azmi Man; Ahmad Sofiman Othman (Tropical Life Sciences Research, 2010)
Weedy rice (WR) is found in many direct-seeded rice fields. WR possesses morphological characteristics that are similar to cultivated rice varieties in the early stage of growth, making them more difficult to control than other weeds. A comparative morphological study was conducted by collecting WR accessions from four sites within the Pulau Pinang rice growing areas. The objective of the study was to characterise WR accessions of the Pulau Pinang rice granary by comparing their morphological characteristics to those of commercially grown rice in the area. Their morphometric relations were established by comparing 17 morphological characteristics of the WR accessions and the commercial varieties. A total of 36 WR morphotypes were identified from these 4 sites based on 17 characteristics, which included grain shattering habit and germination rate. The Principal Component Analysis (PCA) showed that 45.88% of the variation observed among the WR accessions and commercial varieties were within the first 3 axes. PB6, PP2 and SGA5 WR accessions had a higher number of tillers and longer panicle lengths, culm heights and leaf lengths compared to the commercial rice. The grain sizes of the commercial varieties were slightly longer, and the chlorophyll contents at 60– 70 days after sowing (DAS) were higher than those of the WR accessions. Results from this study are useful for predicting potential WR accession growth, which might improve WR management and agriculture practices that control WR in the future. Padi angin boleh ditemui dalam petak sawah yang mengamalkan kaedah tabur terus. Kebanyakan padi angin mempunyai ciri-ciri morfologi yang sama dengan varieti komersial, menyebabkan padi angin sukar dikawal. Satu persampelan aksesi-aksesi padi angin telah dijalankan di empat lokasi jelapang padi Pulau Pinang bertujuan untuk kajian perbandingan ciri-ciri morfologi dengan varieti komersial yang ditanam di lokasi tersebut. Sejumlah 36 varian berbeza telah dikenal pasti dari 4 lokasi melalui perbandingan 17 ciri morfometrik dan sifat penguguran biji dari tangkai serta kadar percambahan biji benih. Analisis Komponen Prinsipal (PCA) menunjukkan bahawa 45.88% taburan variasi aksesi padi angin dan varieti komersial terkandung dalam 3 paksi pertama. Aksesi padi angin seperti PB6, PP2 dan SGA5 mempunyai bilangan anak yang banyak, tangkai padi yang panjang, batang pokok yang tinggi dan daun yang lebih panjang berbanding varieti komersial. Panjang biji padi dan kandungan klorofil pada 60–70 DAS (days after sowing) pada varieti komersial adalah lebih tinggi berbanding aksesi padi angin. Hasil kajian berjaya menentukan kadar pertumbuhan pokok padi angin dan mungkin dapat digunakan dalam pengurusan rumpai di sawah dan amalan pertanian baik.